LOST IN TRANSLATION: PRESENT-DAY TERMS IN THE MAINTENANCE TEXTS OF THE NADIÄ€TU FROM OLD BABYLONIAN NIPPUR - van Wyk, Susandra J (Journal for Semitics, 2017)
Present-day terms such as the usufruct â€“ in civil law systems â€“ and its equivalent, the life-right â€“ in common law systems â€“ were foreign to ancient Near Eastern legal texts. Prima facie both terms â€“ usufruct and life-right â€“ direct the â€œtime-limited interestâ€ of the use and enjoyment by a person over the property of another. However, mainstream ancient Near Eastern scholarsâ€™ unqualified use of the foreign terms â€“ diverged in time and space â€“ affect the translation and our insight into ancient texts. In addition, differences in land ownership institutions and philosophies in present-day law systems and those of ANE contribute to variances in the meaning and interpretation of the intrinsic aspects of property and as such â€œtime-limited interestâ€ applicable: a usufruct, life-right or even a hybrid form of both. In the article, I focus on the maintenance â€“ a time-limited interest â€“ of the nadÄ«tu priestess in the Old Babylonian city-state of Nippur. The application of Stoneâ€™s theory on Nippurâ€™s land ownership â€“ the institutionsâ€™ economy â€“ prima facie shows that the nadiÄtu of Nippur held a freestanding life-right, rather than a usufruct which the majority of ANE scholars assigned to the nadiÄtuâ€™s maintenance. However, I propose a deviation with the superficial overlay of present-day terms on the maintenance of the nadiÄtu by presenting a time-limited interest framework. The framework serves as a delineation method of identifying the characteristics of the maintenance-construction of the nadiÄtu from OB Nippur: communicating a â€œunitary conceptâ€ in context of the ancient texts â€“ rather than only assigning coined terms â€“ taking recognition of the influences of Nippurâ€™s land ownership philosophy.